Spinocerebellar Ataxia 7: A Report of Unaffected Siblings Who Married into Different SCA 7 Families. (4th May 2014) - Zaheer, Fariha; Fee, Dominic
Abstract : Two families with spinocerebellar ataxia type 7 are presented. Although there are affected cousins, it is not the sibling parents that transmitted the mutation. It is assumed that the affected families share a common ancestor.